(untitled) (Ricos Biology, 2025)
Control, management, and eradication of Spodoptera frugiperda or Fall armyworm (FAW) was challenging without the extensive use of inorganic pesticides. However, extensive application of inorganic pesticides threatens human health, animals, and the environment. Hence, natural, organic, and eco-friendly substances are needed to control the proliferation of FAW. The main objective of this study was to determine the effects of Solanum nigrum Linn. or Black nightshade or Am-amsi leaf and fruit aqueous extract to FAW found in Nicotiana tabacum or Burley tobacco plants. Field experimental method using completely randomized design was employed. Data gathered were analyzed through descriptive statistics such as mean and ANOVA. Phytochemical analysis revealed that Black nightshade contains flavonoids, saponins, steroids, and terpenoids. Secondly, FAWs were irritable upon application of Am-amsi aqueous extract and became immobile after 12 hours of application. Moreover, there was an increasing mortality of FAW in the four treatments after 24 to 72 hours of application. In addition, there was a significant difference between T1 or 25% concentration and T4 or 100% concentration after 36 hours; there was a significant difference between T2 or 50% concentration and T4 after 60 hours; and there was a significant difference between T1 and T4 after 72 hours. Finally, Post Hoc analysis showed that T3 or 75% concentration was comparable to T4 when compared to a synthetic insecticide. It has been demonstrated that T4 of the aqueous extract was the most effective against FAW while T3 was comparable to T4 concentration. The phytochemical components of Black nightshade contributed to the irritability, immobility, and mortality of FAW. These findings suggest that Black nightshade is a potential natural and organic larvicide against FAW. Through the use of leaf and fruit extract of Am-amsi, tobacco farmers can control FAW which is safer, more cost-effective, and more eco-friendly pesticide.